Phylogeny and adaptive evolution of subgenus Rhizirideum (Amaryllidaceae, Allium) based on plastid genomes - Xiao Fu; Deng-Feng Xie; Yu-Yang Zhou; Rui-Yu Cheng; Xiang-Yi Zhang; Song-dong Zhou; Xing-Jin He (BMC Plant Biology, 2023)
Abstract The subgenus Rhizirideum in the genus Allium consists of 38 species worldwide and forms five sections (A. sect. Rhizomatosa, A. sect. Tenuissima, A. sect. Rhizirideum, A. sect. Eduardia, and A. sect. Caespitosoprason), A. sect. Caespitosoprason being merged into A. sect. Rhizomatosa recently. Previous studies on this subgenus mainly focused on separate sections. To investigate the inter-section and inter-subgenera phylogenetic relationships and adaptive evolution of A. subg. Rhizirideum, we selected thirteen representative species, which cover five sections of this subgenus and can represent four typical phenotypes of it. We conducted the comparative plastome analysis with our thirteen plastomes. And phylogenetic inferences with CDSs and complete sequences of plastomes of our thirteen species and another fifty-four related species were also performed. As a result, the A. subg. Rhizirideum plastomes were relatively conservative in structure, IR/SC borders, codon usage, and repeat sequence. In phylogenetic results, the inter-subgenera relationships among A. subg. Rhizirideum and other genus Allium subgenera were generally similar to the previous reports. In contrast, the inter-section relationships within our subgenus A. subg. Rhizirideum were newly resolved in this study. A. sect. Rhizomatosa and A. sect. Tenuissima were sister branches, which were then clustered with A. sect. Rhizirideum and A. sect. Eduardia successively. However, Allium Polyrhizum Turcz. ex Regel, type species of A. sect. Caespitosoprason, was resolved as the basal taxon of A. subg. Rhizirideum. Allium siphonanthum J. M. Xu was also found in clade A. subg. Cyathophora instead of clade A. subg. Rhizirideum. The selective pressure analysis was also conducted, and most protein-coding genes were under purifying selection. At the same time, just one gene, ycf2, was found under positive selection, and another three genes (rbcL, ycf1a, ycf1b) presented relaxed selection, which were all involved in the photosynthesis. The low temperature, dry climate, and high altitude of the extreme habitats where A. subg. Rhizirideum species grow might impose intense natural selection forces on their plastome genes for photosynthesis. In summary, our research provides new insights into the phylogeny and adaptive evolution of A. subg. Rhizirideum. Moreover, we suggest that the positions of the A. subg. Rhizirideum species A. polyrhizum and A. siphonanthum should be reconsidered.